If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(x + 1) = 4 + -1(2x + 3) Reorder the terms: 5 + -1(1 + x) = 4 + -1(2x + 3) 5 + (1 * -1 + x * -1) = 4 + -1(2x + 3) 5 + (-1 + -1x) = 4 + -1(2x + 3) Combine like terms: 5 + -1 = 4 4 + -1x = 4 + -1(2x + 3) Reorder the terms: 4 + -1x = 4 + -1(3 + 2x) 4 + -1x = 4 + (3 * -1 + 2x * -1) 4 + -1x = 4 + (-3 + -2x) Combine like terms: 4 + -3 = 1 4 + -1x = 1 + -2x Solving 4 + -1x = 1 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4 + -1x + 2x = 1 + -2x + 2x Combine like terms: -1x + 2x = 1x 4 + 1x = 1 + -2x + 2x Combine like terms: -2x + 2x = 0 4 + 1x = 1 + 0 4 + 1x = 1 Add '-4' to each side of the equation. 4 + -4 + 1x = 1 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = 1 + -4 1x = 1 + -4 Combine like terms: 1 + -4 = -3 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| -3x=-3t-12 | | 2x^2+3= | | 8-8x=93-43x | | -60-9x=-14-9x | | 13d+4=5d+52 | | 73-6x=31 | | 5(x-5)=7.2 | | 3x+9=44 | | -3=-3t-12 | | 6(a+1)=30.6 | | 2u^2-2u-1=0 | | 29.8=4c-5 | | 4e-2=28.4 | | 7p=11.9 | | 56.25=2x^2+y^2 | | 6(x-9)=0 | | p=0.1x^2 | | (x+1).3=(x-2).2 | | 2(a+9)=26 | | p=2X | | 4x+4=3x+5 | | x+4=2x-7 | | (3u^2+2u-1)-(-6u^2+2u+2)+(6u^2+9u+2)= | | 3x-1=7-4(6-2x) | | 6(t+-2)-76=142 | | -5(r-3)-2(2r+1)=-8 | | 4(2b+3)=-3(b-1)+20 | | 36+7.1=2.5b+11.5 | | 4-5x=2x+1 | | 5x+6=3x-6 | | 16t+7=19t+2 | | x^4-8x^2+14=0 |